Molecular characterization and expression analysis of three homoeologous Ta14S genes encoding 14-3-3 proteins in wheat (Triticum aestivum L.) - Xinguo Wang; Yanli Wang; Ruixia Xiao; Xin Chen; Jiangping Ren (Crop Journal, 2016)
The purpose of this study was to characterize Ta14S homoeologs and assess their functions in wheat seed development. The genomic and cDNA sequences of three Ta14S homoeologous genes encoding 14-3-3 proteins were isolated. Sequence analysis revealed that the three homoeologs consisted of five exons and four introns and were very highly conserved in the coding regions and in exon/intron structure, whereas the cDNA sequences were variable in the 5′ and 3′-UTR. The three genes, designated as Ta14S-2A, Ta14S-2B and Ta14S-2D, were located in homoeologous group 2 chromosomes. The polypeptide chains of the three Ta14S genes were highly similar. These genes were most homologous to Hv14A from barley. Real-time quantitative PCR indicated that the three Ta14S genes were differentially expressed in different organs at different developmental stages and all exhibited greater expression in primary roots of 1-day-old germlings than in other tissues. Comparison of the expression patterns of the three homoeologous genes at different times after pollination also revealed that their expression was developmentally regulated. The transcription of Ta14S-2B was clearly higher during seed germination, whereas expressions of Ta14S-2A and Ta14S-2D were up-regulated at the beginning of seed imbibition (0–12 h), but declined thereafter. The results suggested that the three Ta14S homoeologous genes have regulatory roles in seed development and germination.